83.6k views
4 votes
Simplify the expression. (6k^3)^3
6k^6
216k^6
216k^9
6k^27

User AssamGuy
by
4.7k points

2 Answers

0 votes
Hey there!

The correct answer would most likely be:

Because,


(6x^3)^3 = \\ \\ \\ \\ 6x^3(6x^3)(6x^3) = \\ \\ \\ 6(6)(6) = 216 \\ \\ \\ = 3(3) = 9 \\ \\ \\ Answer: 216x^9

Good luck on your assignment and enjoy your day!

~
LoveYourselfFIrst:)

User AndroGeek
by
4.5k points
3 votes
Distribute ^3 to both 6 and k^3

6^3 = 6 x 6 x 6 = 216
(k^3)^3 = k^9 (because you are multiplying k^3 x k^3 x k^3)

216k^9, or C) is your answer


hope this helps
User Florins
by
5.1k points